DOS MUROS DA ESCOLA À ABERTURA PARA A CIDADE - Nascimento, Antônio Coelho de Souza do (2011)
The educational practice at schools is fraught with a traditional posture and banking , as it appears in several works of Freire, although new technologies area introduced into their routine pedagogic. The emphasis on information instead of knowledge building and knowledge actually away the student, particularly in public schools, to the appropriate of significant tools in its preparation. Accordingly, within line of Educational Policy and Managements Educational, this study proposes a reflection of the school space in the dialogue with the city, namely, the possibility of social protagonism in student development.The research procedure is based on the study of environment education projects developed in the municipal network of Maua through the records and descriptive accounts of evaluations of the schools these activities, their Political Pedagogical Project and the Environment Education Program of Maua in Municipal Secretary of Education. The study Of the school walls opening to the city was developed to understand the geographic space, and considering their territorial concept of symbolic space. Thus, we can understand how the relation school/space-territory and Environment Education Program developed in public network schools of the city of Maua appears in the performance of one relative to another. The methodology of work used was exploratory, of bibliographic nature and documental. The research sought to understand the dialogic approach namely established with the city from the conceptualization of the symbolic space of the school in teaching-learning process. The Environment Education Program and the schools, according to its Political and Pedagogic Projects are proposed, although empirically, the work in this direction. The pedagogical practice, as demonstrated by some activities, while treating the theme with no conscience differentiated , indicates an advance in that direction. The texts collectives, solidary participation, are elements that allow us to conclude so. Children s responses were significant, although we have appointed the difficulties in execution of teaching procedures. As this something new not just by the Environment Education Program required capacity to handle action integrated and integrative, in other words, change of subjectivity of the various actors involved in process. The theme could become overly extensive and, thus, lost in generalities. Thus, some relevant aspects were mentioned, without, however, starting to develop further to ensure the objectivity of the study. The school institution is present of the body and soul in the city, and although the environment thematic is present in your routine it makes a formal and informative. Everyone talks about the environment, however few the values of the healthy environment and fit for human development that produces most of the richness of nations. Regarded the comments pointed out, the study presented elements that must be examined more property, namely, with a greater extent, as a proposal for continued of the research.